Structural, Vibrational and Electronic Properties of Small Group IV Oxide Clusters in Lower and Higher Spin State: A DFT Study (Journal of Atomic and Molecular Sciences, 2012)
Structural, vibrational and electronic properties of the zirconium oxide clusters [n=1-6] are calculated to investigate the changes in, lower and higher state by Density functional theory with the B3LYP exchange-correlation functional using LANL2DZ as the basis set. We optimize several isomers for each size in order to obtain the lowest energy structures and to understand the growth behavior. In the next step, these optimized geometries are used to calculate the binding energy and HOMO-LUMO gap (band gap) of the clusters. In all cases ring type structures are found to be most favorable but for n = 3-6, the ring structures are not planar suggesting that the bonding nature in these cluster has some covalent character.